PENGARUH PROGRAM PENGAJARAN REMEDIAL TERHADAP PRESTASI BELAJAR SISWA DI SD NEGERI CARINGIN 02 - Siti Syifa Awalyah; Rusdi Kasman; Abristadevi Abristadevi (Universitas Pahlawan Tuanku Tambusai, 2022)
In the learning process, there will always be various problems, such as students who have difficulty in learning, causing low student achievement. One way that can be used to help students who have difficulties in learning is by providing learning assistance in the form of remedial teaching. Through remedial teaching, it is expected to be able to improve student achievement which is quite low. This study aims to determine the effect of remedial teaching on student achievement before and after remedial at SD Negeri Caringin 02. The variables in this study were remedial teaching as the independent variable and student achievement as the dependent variable. The population is all students of SD Negeri Caringin 02 which consists of 254 students. The sampling technique used was the purposive sampling technique with the criteria for the test results of students who did not reach the KKM as many as 40 students. The data collection technique used is documentation, namely student achievement data on the final exam for PAI subjects. The data analysis technique used is the Paired Sample T-Test. Based on the results of data analysis that has been carried out, the results of the Paired Sample T-Test test obtained the sig value. (2-tailed) of 0.000 where this value is smaller than 0.05 or 0.000 <0.05. The average value before remedial implementation was 69.53 and the average after remedial implementation was 79.08. This means that with the implementation of remedial teaching, student achievement will increase. So it can be concluded that the remedial teaching variable has a significant effect on student achievement. Keywords: Remedial Teaching, Student Achievement